2017
DOI: 10.1002/2016jd025445
|View full text |Cite
|
Sign up to set email alerts
|

Production mechanisms of leptons, photons, and hadrons and their possible feedback close to lightning leaders

Abstract: It has been discussed that lightning flashes emit high‐energy electrons, positrons, photons, and neutrons with single energies of several tens of MeV. In the first part of this paper we study the absorption of neutron beams in the atmosphere. We initiate neutron beams of initial energies of 350 keV, 10 MeV, and 20 MeV at source altitudes of 4 km and 16 km upward and downward and see that in all these cases neutrons reach ground altitudes and that the cross‐section areas extend to several km2. We estimate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 67 publications
0
19
0
2
Order By: Relevance
“…Various measurements have shown that electric fields in streamer discharges can reach field strengths of up to ≈10 E k (Kim et al, 2004; Pancheshnyi et al, 2000; Spyrou & Manassis, 1989) consistent with results of streamer simulations and analytic estimates (Chanrion & Neubert, 2008; Köhn et al, 2018; Liu & Pasko, 2004; Moss et al, 2006; Naidis, 2009; Qin & Pasko, 2014; Tholin & Bourdon, 2013). In the vicinity of lightning leader tips, calculations have shown that the enhanced electric field can exceed several times the breakdown field (Köhn, Diniz, Harakeh, 2017; Köhn & Ebert, 2015). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various measurements have shown that electric fields in streamer discharges can reach field strengths of up to ≈10 E k (Kim et al, 2004; Pancheshnyi et al, 2000; Spyrou & Manassis, 1989) consistent with results of streamer simulations and analytic estimates (Chanrion & Neubert, 2008; Köhn et al, 2018; Liu & Pasko, 2004; Moss et al, 2006; Naidis, 2009; Qin & Pasko, 2014; Tholin & Bourdon, 2013). In the vicinity of lightning leader tips, calculations have shown that the enhanced electric field can exceed several times the breakdown field (Köhn, Diniz, Harakeh, 2017; Köhn & Ebert, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…One is that seed electrons from cosmic ray ionization of the atmosphere are born with energies in the runaway regime and are further accelerated by the ambient electric field in a cloud, forming a relativistic runaway electron avalanche (RREA; Babich et al, 2012; Dwyer, 2003; Gurevich et al, 1992; Gurevich & Karashtin, 2013; Wilson, 1925) including the feedback mechanism where high‐energy electrons produce high‐energy gamma rays through the bremsstrahlung process which subsequently produces secondary electrons and positrons through photoionization, Compton scattering, or pair production (Dwyer, 2003, 2007; Kutsyk et al, 2011; Skeltved et al, 2014). The other is that thermal (cold) electrons are accelerated into the runaway regime in the high, but very localized, field of streamer tips as well as by the enhanced electric fields in the vicinity of lightning leader tips (Babich et al, 2015; Celestin & Pasko, 2011; Chanrion & Neubert, 2008; Köhn et al, 2014; Köhn & Ebert, 2015; Köhn, Diniz, Harakeh, 2017) and subsequently turn into relativistic RREAs (Carlson et al, 2010, 2006; Köhn, Diniz, Harakeh, 2017; Moss et al, 2006). In the following we explore the streamer mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…They diffuse isotropically while losing energy through collisions. Their attenuation length is ∼685 m (Köhn et al, ). This concept is consistent with the simulated distribution of photons and neutrons in space, time, and energy.…”
Section: Simulated Photon and Neutron Distributions In Space Time Amentioning
confidence: 99%
“…The effective value of E c may be significantly lower, as electrons could overcome the friction barrier due to their intrinsic random interactions (Lehtinen et al, 1999;Li et al, 2009;Liu et al, 2016;Chanrion et al, 2016). Cold runaway could happen in the streamer phase (Moss et al, 2006;Li et al, 2009;Chanrion and Neubert, 2010) or leader phase (Celestin and Pasko, 2011;Celestin et al, 2012;Chanrion et al, 2014;Köhn et al, 2014Köhn et al, , 2017Köhn and Ebert, 2015) of a transient discharge, explaining the high-energy electron seeding that will evolve to RREAs and produce γ rays by bremsstrahlung emission from the accelerated electrons. The cold runaway mechanism may be further investigated with laboratory experiments, in high-voltage and pulsed plasma technology, and may be linked to the not fully understood X-ray emissions that have been observed during nanosecond pulsed discharge and the formation of long sparks Shao et al, 2011;Kochkin et al, 2016, and references therein), with different possible production mechanisms that were proposed and tested using analytical modelling (Cooray et al, 2009) and computer simulations (Ihaddadene and Celestin, 2015;Luque, 2017;Lehtinen and Østgaard, 2018).…”
Section: Phenomena and Observations In High-energy Atmospheric Physicsmentioning
confidence: 99%